Cell Injury - Sondos, Elthram (Libyan International Medical University Faculty of Pharmacy, 2018)
Normal cells have a fairly narrow range of function or steady state. Excess physiologic or pathologic stress may force the cell to a new steady state that is called Adaptation.
Debrifing
Keywords: pharm-D; Debrifing; The second year